Anterior graft migration in posterior lumbar interbody fusion: A case report and literature review - Masanori Hashimoto; Hirohito Hirata; Masatsugu Tsukamoto; Yoshihara Tomohito; Masaaki Mawatari; Tadatsugu Morimoto (Clinical Case Reports, 2023)
Key Clinical Message Spine surgeons should be aware of the possibility of anterior displacement of the grafted bone during PLIF and the potential for severe complications that may arise because of such displacement so that preparations can be made for a proper response. Abstract We report two cases of anterior displacement of the grafted bone after posterior lumbar interbody fusion (Graphical Abstract A‐D). The patients did not require additional surgery. The anterior migration of grafted bone or cage can cause damage to anterior organs and blood vessels. Therefore, a careful surgical procedure is necessary.